2018
DOI: 10.12804/revistas.urosario.edu.co/sociojuridicos/a.6817
|View full text |Cite
|
Sign up to set email alerts
|

Convertirse en El Más Malo: trayectorias masculinas de violencia en las pandillas de Medellín

Abstract: Con base en 40 entrevistas de historias de vida con miembros de las pandillas de Medellín, Colombia, la presente investigación argumenta que muchos jóvenes se unen a las pandillas con el fin de emular y reproducir identidades masculinas que se consideran localmente ‘exitosas’. La acumulación de ‘capital masculino’ por parte de las pandillas, con sus significantes materiales y simbólicos de hombría, acompañados de demostraciones y manifestaciones estilísticas, lleva a los jóvenes a percibirlas como espacios de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The low/high threshold-tolerance of violence has also been a common focus of attention to analyze how violent acts are minimized and normalized both in daily routines (Heilman & Barker, 2018;Launius & Hassel, 2015) and extraordinary circumstances (Roy, 2008). Moreover, ethnographic fieldwork has illustrated how homicide perpetration is closely associated with specific forms of masculinity which are negotiated as a part of identity formation (Baird, 2018(Baird, , 2019. Phenomenological research has shown that IPV and intimate femicide are a response to a triad of experiences: being bullied as a child, having emotionally absent fathers, and low self-esteem (Lien & Lorentzen, 2019;Ward, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The low/high threshold-tolerance of violence has also been a common focus of attention to analyze how violent acts are minimized and normalized both in daily routines (Heilman & Barker, 2018;Launius & Hassel, 2015) and extraordinary circumstances (Roy, 2008). Moreover, ethnographic fieldwork has illustrated how homicide perpetration is closely associated with specific forms of masculinity which are negotiated as a part of identity formation (Baird, 2018(Baird, , 2019. Phenomenological research has shown that IPV and intimate femicide are a response to a triad of experiences: being bullied as a child, having emotionally absent fathers, and low self-esteem (Lien & Lorentzen, 2019;Ward, 2008).…”
Section: Introductionmentioning
confidence: 99%